IMPROVING STUDENTâS SPEAKING SKILL THROUGH COMMUNICATIVE ENGLISH FOR SPECIFIC PURPOSES - Dewi, Riyana (Orbith, 2016)
The study discusses more about the important role of English for Specific purposes which is needed by the students in uttering the language performance. The objective of this research is to improve the students speaking skill through the learning of English for specific purposes based on the communicative competence. The communicative competence plays the main role in supporting the studentsâ performance in using the English for specific purposes in various professional activities.The researcher uses a classroom action research to conduct the research. Classroom action research is a research which provides problem solving for improving the quality of teaching given to action in the classroom (Burns, 2010:2). The implication of the study should give a great motivation to the students to perform their English speaking skills communicatively. The students, hopefully, will communicate English actively and feel happy in using the English as a means of communication.Keywords: English for specific purposes, communicative competence, classroom action research